A Note on Production of High Alpha Cellulose Pulp from Leucaena leucocephala - Sharma, Y. K.; Mahajan, Sushma; Bhola, P. P. (Indian Forester, 1984)
The present investigation reveals that the Su-babul can be utilised for the production of alpha-cellulose. The chemical purity shows that the raw material is suitable for preparing cellophane and textile in high yield (39.8%).